Optimization of corona ring for 230 kV polymeric insulator based on finite element method and PSO algorithm - Diaz-Acevedo, Jairo A.; Escobar, Adolfo; Grisales-Noreña, Luis F. (Electric power systems research, 2021)
•Corona rings reduce the electric field at critical zones of polymeric insulators.•Corona ring design impacts the electric field at the energized-end fitting.•Ring tube diameter is the parameter that most affects the electric field reduction.•FEM, along with the PSO algorithm, allows optimizing the corona ring design. The electric field distribution is a very important factor in the performance of polymeric insulators. This distribution varies under different operating conditions. Therefore, there are different approaches to reduce the electric field strength at the critical zones to acceptable values. One of these approaches is the use of corona rings. However, the design of corona rings is not standardized, and the geometric parameters affect the electric field distribution. This work analyzed the relationship between corona ring design parameters and the electric field strength near energized-end fitting in a real 230 kV polymeric insulator with a corona ring. First, it was used the Finite Element Method to evaluate the influence of three corona ring design parameters on the electric field strength: corona ring diameter, ring tube diameter, and corona ring position. Then, the PSO algorithm was used to optimize the original corona ring and reduce the electric field strength at three critical zones: triple point, the surface of the energized-end fitting, and the surface of the corona ring. The optimization process reduced the maximum electric field strength by 50.5% relative to the insulator with the original corona ring (82.4% without a corona ring).